Volume 7: Ocean Engineering 2016
DOI: 10.1115/omae2016-54163
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Rankine Panel Method for Seakeeping Prediction of a Ship in Low Frequency Region

Abstract: Rankine panel methods have been studied for solving 3D seakeeping problems of a ship with forward speed and oscillatory motions. Nevertheless, there is a drawback in the numerical method for satisfying the radiation condition of outgoing waves at low frequencies, because the waves generated ahead of a ship reflect from the outward computational boundary and smear the flow around the ship. The so-called panel shift technique has been adopted in the frequency-domain Rankine panel method, which is effective when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The superiority of ver. 7 was confirmed through this test, as will be described later, so the same investigation was conducted on the RIOS bulk carrier model, for which much data have been accumulated [4,6,26].…”
Section: Towing Tank Testsmentioning
confidence: 61%
See 2 more Smart Citations
“…The superiority of ver. 7 was confirmed through this test, as will be described later, so the same investigation was conducted on the RIOS bulk carrier model, for which much data have been accumulated [4,6,26].…”
Section: Towing Tank Testsmentioning
confidence: 61%
“…The value of C f is given so that the slope is equal to that of the Pressure [N/m 2 ] Fig. 4 An example of calibration outputs from an FBG pressure sensor hydrostatic pressure g z ( : density of water, g: gravitational acceleration, z : sinkage), which is illustrated by the red line in Fig. 4.…”
Section: Calibration Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other categories of radiation condition applicable to low forward speed problem have been proposed and validated recently. Yasuda et al [16] introduced Rayleigh's artificial friction in the boundary condition to suppress longer wave components in a computational region apart from the ship. Their simulation results showed that wave reflection from upstream boundary was very limited and good agreement with measured results was obtained as a result.…”
Section: Introductionmentioning
confidence: 99%